Project Planning and Scheduling - Haugan, Gregory (Berrett-Koehler Publishers, 2001)
This is the only book that makes all planning methods and tools available to project managers at all levels easy to understand ... and use. Instead of applying techniques piecemeal, you'll take a cohesive, step-by-step approach to improve strategic and operational planning and scheduling throughout the organization. You'll master advanced scheduling techniques and tools such as strategic planning models and critical chain and enterprise project management. Includes time-and-error-saving checklists.